Assessment of DNA damage in women using oral contraceptives by using comet assay - Shalish, Worood K. (Iraqi Journal of Cancer and Medical Genetics, 2014)
This study includes the investigation of oral contraceptives pills effect (Yasmin) on women who used the contraceptive pills by measuring the percentage of DNA damage. Comparison process depends on evaluation of DNA damage percentage on blood lymphocytes in women who used the contraceptive pills for different periods by using comet assay. The presented results obtained from 25 women handling contraceptive pills and 15 women who had not used the pills. The samples were divided into two groups according to the period of contraceptive pills treatment to (2-5) years and (6-8) years. Using image analysis software score comet, three parameters for measuring DNA damage were estimated to indicate it. DNA parameters were tail length, tail DNA % and tail moment. The results showed that the mean of tails lengths of comet in women who used birth control pills (2-5) years were (19.13%) while in women who used birth control pills (6-8) years were (25.08%). The observed values were significantly different (P≤0.05) from those in control, which were (0.8%). On the other hand, the percentage of DNA in the tail and tail moments of comet in women with contraceptive pills treatment (2-5) years were (20.12%) and (23.63%) respectively, while in women with contraceptive pills treatment (6-8) years were (28.63%) and (31.81%) respectively and the observed values were significantly different (P≤0.05) from those in control, which were (1.6%) of DNA in the tail and (0.01%) of tail moments. It is concluded from these results that the prolonged use of contraceptive drugs in our daily life will increase the percentage of DNA damage.